Standardization parameters for production of tofu using WSD-Y-1 machine (Journal of the Bangladesh Agricultural University, 2014)
The present work was aimed to standardize different parameters for tofu production using the WSD-Y-1 machine. For this purpose the coagulant variation for production of tofu, shelf life of produced tofu as well as capacity of different parts of the WSD-Y-1 machine was determined. Soybean sample was collected from the Givency Pvt. Ltd., Gazipur. Soymilk was prepared by using the WSD-Y-1 machine. Seven tofu samples were prepared by using different coagulants (CaSO4, MgSO4). TSS variation of the milk was also made. The storage stability of tofu was observed at both room temperature and refrigeration temperature. The yield of tofu varied with coagulants. It was observed that the calcium sulfate gave more yield than magnesium sulfate when the use of both of the coagulants exceeded the single use. Tofu can be kept fresh under water up to one and half of a day and in the refrigerator up to ten days. The operating system of the WSD-Y-1 machine was standardized carefully. There were three operating parts: grinding, heating, and pressing. The grinder was capable to grind about 12-13 kg soybeans at a time. About 45 liter of milk can be heated in the heating system while in the pressing system about 14 liter of milk can be kept for pressing at a time. In this experiment about 1.2 kg of tofu was produced from 1 kg of soybean. On the basis of the work it is recommended that good quality of tofu can be prepared by using the WSD-Y-1 machine which is superior in quality to the hand-made ones. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19930 J. Bangladesh Agril. Univ. 11(2): 307-312, 2013